Evaluating the ASTHMAXcel Mobile Application Regarding Asthma Knowledge and Clinical Outcomes. - Hsia, Brian C.; Wu, Sammy; Mowrey, Wenzhu B.; Jariwala, Sunit P. (Respiratory Care, 2020)
BACKGROUND: We sought to longitudinally assess the efficacy of the patient-facing ASTHMAXcel mobile application in improving asthma knowledge and outcomes in adults with asthma. METHODS: ASTHMAXcel is a novel smartphone application consistent with the National Asthma Education and Prevention Program, Global Initiative for Asthma, and British Thoracic Society/Scottish Intercollegiate Guidelines Network guidelines. The intervention was provided for 1-time use at baseline only. The Asthma Knowledge Questionnaire (AKQ), the Asthma Control Test (ACT), and the mini-Asthma Quality of Life Questionnaire (mini-AQLQ) were administered at baseline and at 2, 4, and 6 months thereafter. Rates of asthma-related emergency department visits, hospitalizations, and prednisone use were also evaluated. RESULTS: ACT scores increased significantly at 2, 4, and 6 months (mean scores: 15.1 vs 16.9, P = .038; 15.1 vs 17.2, P = .02; 15.1 vs 17.9, P = .003) after baseline. There were significant increases in AKQ scores at 4 and 6 months (11.7 vs 12.6, P = .02; 11.7 vs 13.1, P = .005) and in mini-AQLQ scores at 6 months (55.5 vs 64.2, P = .02). There were significant decreases in asthma-related emergency department visits at 6 months (0.6 vs 0, P < .001) and in hospitalizations at 4 and 6 months (0.3 vs 0.1, P = .02; 0.3 vs 0, P = .002). Prednisone use decreased at 4 and 6 months (1.2 vs 0.6, P = .01; 1.2 vs 0.3, P < .001). CONCLUSIONS: ASTHMAXcel contributes to improved asthma knowledge and outcomes and to decreased health care utilization. ASTHMAXcel is an inexpensive, scalable aid for out-patient asthma management.